2019
DOI: 10.1097/op9.0000000000000011
|View full text |Cite
|
Sign up to set email alerts
|

Pharmaceutical consultations in oncology: French Society for Oncology Pharmacy (Société Francaise de Pharmacie Oncologique – SFPO) guidelines

Abstract: Introduction: Pharmaceutical consultations is a key point for oral therapy-treated cancer patients’ management. Methods: French Society for Oncology Pharmacy built recommendations according to French High Authority of Health regarding the guidelines for Good Practice. Results: Fourteen guidelines were issued and tools proposed to hospital pharmacist's community. Discussion: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Prompt implementation of clinical pharmacy in COVID-19+ units contributes to treatment optimization in the face of a theoretical risk of drug-related iatrogenesis in this novel population -risk also run by cancer patients in the COVID-19 context. The benefit of pharmaceutical expertise in cancer is well-established [110][111][112], and the pandemic has led to adaptation of oncology clinical pharmacy activity: an organizational approach to limit contact-time in the care units (pharmaceutical care including consultations, medication reconciliation) and a pharmacologic approach (medication prescription analysis). Neither approach needs to be short-term with a return to business-as-usual envisaged within a matter of weeks: medium and even long-term perspectives are possible.…”
Section: Guidelines For the Practice Of Oncology Clinical Pharmacy Under The Covid-19 Pandemicmentioning
confidence: 99%
“…Prompt implementation of clinical pharmacy in COVID-19+ units contributes to treatment optimization in the face of a theoretical risk of drug-related iatrogenesis in this novel population -risk also run by cancer patients in the COVID-19 context. The benefit of pharmaceutical expertise in cancer is well-established [110][111][112], and the pandemic has led to adaptation of oncology clinical pharmacy activity: an organizational approach to limit contact-time in the care units (pharmaceutical care including consultations, medication reconciliation) and a pharmacologic approach (medication prescription analysis). Neither approach needs to be short-term with a return to business-as-usual envisaged within a matter of weeks: medium and even long-term perspectives are possible.…”
Section: Guidelines For the Practice Of Oncology Clinical Pharmacy Under The Covid-19 Pandemicmentioning
confidence: 99%
“…12: Oncologic clinical pharmacy activities are maintained. 40,42,43,53 These activities make it possible to optimize the therapeutic care of the patient with cancer.…”
Section: Guidelinesmentioning
confidence: 99%
“…[40][41][42][43] Pharmaceutical consultations contribute to the optimal management of the patient with cancer. 53 Reducing contact with at-risk patients, such as patients with cancer, requires telephone consultations or teleconsultations. 2,20,26,28 Increased attention will be paid to the initiation of treatment.…”
Section: Guidelinesmentioning
confidence: 99%
See 1 more Smart Citation
“…21 The French Society of Oncology Pharmacy (Société Française de Pharmacie Oncologique) recommends the involvement of an oncology pharmacist in this type of follow-up and especially in the management of OATs. 22 Several studies 23 have shown a positive effect on treatment adherence among patients receiving a pharmaceutical consultation as part of a multidisciplinary consultation program (MCP). The program's main objective to increase treatment safety and efficacy 24 by educating the patient and providing drug information.…”
Section: Introductionmentioning
confidence: 99%